2005
DOI: 10.1186/1471-2296-6-25
|View full text |Cite
|
Sign up to set email alerts
|

The DiGEM trial protocol – a randomised controlled trial to determine the effect on glycaemic control of different strategies of blood glucose self-monitoring in people with type 2 diabetes [ISRCTN47464659]

Abstract: BackgroundWe do not yet know how to use blood glucose self-monitoring (BGSM) most effectively in the self-management of type 2 diabetes treated with oral medication. Training in monitoring may be most effective in improving glycaemic control and well being when results are linked to behavioural change.Methods/designDiGEM is a three arm randomised parallel group trial set in UK general practices. A total of 450 patients with type 2 diabetes managed with lifestyle or oral glucose lowering medication are included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…The trial was managed from the coordinating centre at the Department of Primary Health Care, University of Oxford. 9 Our primary aim was to determine whether haemoglobin A 1c (HbA 1c ) levels at 12 months were significantly different between patients with non-insulin treated type 2 diabetes receiving one of three allocated interventions: standardised usual care with measurements of HbA 1c levels by health professionals every three months (control group); use of a blood glucose meter, with advice for participants to contact their doctor for interpretation of results (less intensive self monitoring); and use of a blood glucose meter with training in self interpretation and application of the results to diet, physical activity, and drug adherence (more intensive self monitoring).…”
Section: Methodsmentioning
confidence: 99%
“…The trial was managed from the coordinating centre at the Department of Primary Health Care, University of Oxford. 9 Our primary aim was to determine whether haemoglobin A 1c (HbA 1c ) levels at 12 months were significantly different between patients with non-insulin treated type 2 diabetes receiving one of three allocated interventions: standardised usual care with measurements of HbA 1c levels by health professionals every three months (control group); use of a blood glucose meter, with advice for participants to contact their doctor for interpretation of results (less intensive self monitoring); and use of a blood glucose meter with training in self interpretation and application of the results to diet, physical activity, and drug adherence (more intensive self monitoring).…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for this comparator has been set out elsewhere. 26 It is possible, however, that in some settings patients are not receiving care to the standards of current practice guidelines. Provision of care in accordance with current recommendations should be a priority.…”
Section: Implications For Clinicians and Policymakersmentioning
confidence: 99%
“…One such a trial may be the DiGEM (Diabetes Glycemic Education and Monitoring) study, the findings from which are due to be reported in 2007. DiGEM should establish whether SMBG is effective over a 12-month period when results are 1) interpreted by the patient and applied to lifestyle (selfmonitoring group), in addition to 2) nurse-practitioner interpretation to inform medication adjustment (self-testing group), compared with, and in addition to, 3) standardized usual care and 3-monthly A1C measurements (control group) (48). Non-insulin-treated type 2 diabetic patients aged Ն25 years are eligible.…”
Section: Longitudinal Cohortmentioning
confidence: 99%